KARAKTERISTIK PEMAKAIAN TENAGA SURYA PADA MODUL SOLAR SMART SEBAGAI IMPLEMENTASI DARI LISTRIK KERAKYATAN - Jurnal, Redaksi Tim (ENERGI & KELISTRIKAN, 2019)
Solar Street Lighting Light (PJU-TS) is a street lighting that uses sunlight as a source of electrical energy. The Solar Street Lighting (PJU-TS) is very suitable for roads in areas not covered by PLN electricity and also areas experiencing electrical energy crisis especially in remote areas. But recently PJU Solar Power is also rife applied in urban areas such as in the main streets, residential street, garden lights, campus area, factory area, bus stops, parking lots, gas stations (gas stations) and so on. In the process of designing the lamps for the first PJU is to determine the load installed, then calculate the number of solar panels or photovoltaic needs, then calculate the battery requirements and determine the capacity of the battery charge regulator (BCR). Then for PJU lamps to operate automatically installed light sensor or light dependent resistor (LDR) as a switch to turn on and off PJU lights. Then after all in the know then in the process of development researchers observed about how the performance of the controller in terms of automatic mode, manually circuit and its equipment components as well as sensors and modems. From there sought characteristics of each.